The Q-Academic system and the challenges of teachers and students for online interaction (Research, Society and Development, 2020)
With the advancement of technology, the emergence of interactive online spaces is increasingly present in people's daily lives. With school could not be different. We verified different software used in education with the purpose of facilitating the interaction of the school community, however the number of studies that contemplate this theme is not very expressive yet. Considering this context, our proposal aims to discuss the challenges of interaction between teachers and students via Q-Academic at IFMT. To support our discussions, we start from the teacher training assumptions of Nóvoa (2007) and Paris et all (1984) and the teacher education studies for digital context by Coscarelli (2007) and Xavier (2003). The qualitative methodology had two phases: in the first one we applied a questionnaire with open and closed questions, in teachers and students, about the use of the Q-Academic Message and Classroom tools, and, in the second, we proceeded to the analysis of the collected results. With this study, we hope to weave the interaction profile between teachers and students and to verify the challenges of using these Q-Academic tools, thus contributing for the IFMT school community to take advantage of the resources available in this environment, improving the teaching-learning process at IFMT.